Detection and quantification of boscalid and its metabolites in honeybees. (August 2016) - Jabot, Claire; Daniele, Gaëlle; Giroud, Barbara; Tchamitchian, Sylvie; Belzunces, Luc P.; Casabianca, Hervé; Vulliet, Emmanuelle
Abstract: Boscalid is a new-generation fungicide that has been detected in several bee matrices. The objective of this work was to characterize boscalid metabolites in honeybees based on in vivo experimentation, and next to verify the presence of theses metabolites into honeybees from colonies presenting troubles. A methodology based on complementary mass spectrometric tools, namely ultra-high performance liquid chromatography coupled to high-resolution mass spectrometry (UHPLC-QToF) or triple quadrupole mass spectrometry (UHPLC-QqQ) was implemented. Honeybees were sprayed with boscalid, at field rate (to induce the metabolization process) and the parent compound with its generated metabolites were then extracted using modified EU-QuEChERS method. The mass characteristics including exact mass, isotopic profile and mass fragments allowed assuming the structure of several metabolites. Some of them were unambiguously identified by comparison with synthesized analytical standards. The metabolites were resulted from hydroxylation and dechlorination of the parent compound as well as the substitution of a chlorine atom with an hydroxyl group. The metabolites were then quantified in bee samples collected from various beehives located in France. Boscalid and three of its metabolites were present in some samples at a level ranged between 0.2 and 36.3 ng/g. Graphical abstract: Highlights: Methodology based on the use of both high- and low-resolution mass spectrometry. Identification for the first time of boscalid metabolites in honeybees. Quantification of boscalid and three metabolites in honeybees collected in hives.